Semi-transparent and stable In2S3/CdTe heterojunction photoanodes for unbiased photoelectrochemical water splitting - Yuan Cai; Shujie Wang; Bin Liu; Gong Zhang; Hui Gao; Yuting Tong; Qingfeng Chang; Peng Zhang; Tuo Wang; Jinlong Gong (Nature Communications)
Abstract The development of low-cost, high-performance, and stable photoanodes is essential for solar-driven photoelectrochemical energy conversion. In2S3, an n-type semi-transparent semiconductor (~2.0 eV), is particularly well-suited as a photoanode in PEC tandem devices. However, the Schottky barrier at the In2S3/FTO interface as well as the inherent defects in In2S3 suppress charge extraction. This paper describes the design of a semi-transparent photoanode aimed at enhancing carrier mobility for unassisted water splitting. We incorporate a semi-transparent Ag layer at the FTO/In2S3 interface to establish an ohmic contact, effectively resolving the conflict between light shielding of metal and the electron collection barrier from In2S3 to FTO. Additionally, the In2S3/CdTe p-n heterojunction forms an effective built-in electric field, which serves as a strong driving force for the separation and migration of photogenerated charges. The Ag/Ag:In2S3/In2S3/CdTe/NiO x /TiO2/Ni semi-transparent photoanode exhibits a photocurrent density of 12.2 mA/cm2 at 1.23 V vs. reversible hydrogen electrode, with stable operation for 60 h. Pairing a back-illuminated Si photocathode with an In2S3/CdTe semi-transparent photoanode enables a solar-to-hydrogen conversion efficiency of 5.10%.